Azərbaycan : Aylık Kültür Dergisi | 1989 | Sayı: 270 - Azərbaycan Kültür Derneği (Azərbaycan Kültür Derneği yayım Organı, 1989)
Turkish Cultural periodical of Azerbaijanian Turks was established since 1952. "Azərbaycan Kültür Dergisi" was published for support of Azerbaijani independence movement and cultural matters.
Keywords: Azerbaijani journals.; Journalism -- Azerbaijan.; Azerbaijan -- History -- 20th century.; Azerbaijani culture.